Strategi Promosi dan Pemasaran Layanan di Perpustakaan pada Era Society 5.0: Systematic Literature Review - Anggraeni, Novita Cristyne; Laksmi, Laksmi (Media Pustakawan, 2025)
The emergence of Society 5.0 demands that libraries innovate in their promotional strategies to adapt to digital transformation and shifting user behaviors. This study aims to identify the promotional strategies employed by libraries and the challenges encountered in their implementation. Utilizing a Systematic Literature Review (SLR) approach, this research analyzed 12 peer-reviewed articles published between 2017 and 2023, sourced from the ProQuest database. The findings reveal that libraries have adopted a variety of promotional techniques, including the use of social media, library exhibitions, promotional products (such as websites and email services), and special programs or events like user orientations and seminars. Among these, social media platforms—particularly Facebook, WhatsApp, and YouTube—are the most frequently utilized tools. However, several challenges persist, including inadequate infrastructure, the absence of institutional regulations, limited budget allocations, and insufficient technical competencies among librarians in managing digital promotion tools. This study concludes that while libraries have made considerable efforts to adapt promotional strategies in the digital era, institutional support and capacity-building initiatives for librarians are crucial to enhancing the effectiveness and sustainability of library marketing practices.